PENGABDIAN KEPADA MASYARAKAT PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI INTERNET DAN WEB GOVERMNET BAGI APARATUR DESA (LP3K Lampung, 2021)
Technology is a form of development. All humans on earth are forced to open their eyes to technological changes that are so fast and affect all aspects of life. Inpres no 3 of 2003 formulated that the goal of e-Government development is an effort to develop (using) electronic-based governance in order to improve the quality of public services effectively and efficiently. Training on the use of Information Technology for the Pekon apparatus in Pringsewu Regency will provide additional knowledge regarding the functions and benefits of implementing e-government.